Variation in NAT2 acetylation phenotypes is associated with differences in food-producing subsistence modes and ecoregions in Africa - Podgorná, Eliška; Diallo, Issa; Vangenot, Christelle; Sanchez-Mazas, Alicia; Sabbagh, Audrey; Černý, Viktor; Poloni, Estella S (BMC evolutionary biology, 2015)
BACKGROUND: Dietary changes associated to shifts in subsistence strategies during human evolution may have induced new selective pressures on phenotypes, as currently held for lactase persistence. Similar hypotheses exist for arylamine N-acetyltransferase 2 (NAT2) mediated acetylation capacity, a well-known pharmacogenetic trait with wide inter-individual variation explained by polymorphisms in the NAT2 gene. The environmental causative factor (if any) driving its evolution is as yet unknown, but significant differences in prevalence of acetylation phenotypes are found between hunter-gatherer and food-producing populations, both in sub-Saharan Africa and worldwide, and between agriculturalists and pastoralists in Central Asia. These two subsistence strategies also prevail among sympatric populations of the African Sahel, but knowledge on NAT2 variation among African pastoral nomads was up to now very scarce. Here we addressed the hypothesis of different selective pressures associated to the agriculturalist or pastoralist lifestyles having acted on the evolution of NAT2 by sequencing the gene in 287 individuals from five pastoralist and one agriculturalist Sahelian populations. RESULTS: We show that the significant NAT2 genetic structure of African populations is mainly due to frequency differences of three major haplotypes, two of which are categorized as decreased function alleles (NAT2*5B and NAT2*6A), particularly common in populations living in arid environments, and one fast allele (NAT2*12A), more frequently detected in populations living in tropical humid environments. This genetic structure does associate more strongly with a classification of populations according to ecoregions than to subsistence strategies, mainly because most Sahelian and East African populations display little to no genetic differentiation between them, although both regions hold nomadic or semi-nomadic pastoralist and sedentary agriculturalist communities. Furthermore, we found significantly higher predicted proportions of slow acetylators in pastoralists than in agriculturalists, but also among food-producing populations living in the Sahelian and dry savanna zones than in those living in humid environments, irrespective of their mode of subsistence. CONCLUSION: Our results suggest a possible independent influence of both the dietary habits associated with subsistence modes and the chemical environment associated with climatic zones and biomes on the evolution of NAT2 diversity in sub-Saharan African populations.
Keywords: Arylamine N-Acetyltransferase; Molecular Biology; Africa South of the Sahara; Haplotypes; populační genetika; Genetics, Population; Genetics, Medical; polymorfismus genetický; subsaharská Afrika; Polymorphism, Genetic; Humans; Food; molekulární biologie; Black People; haplotypy; černoši; acetylace; Acetylation; arylamin-N-acetyltransferasa; potraviny; lidé; lékařská genetika